The role of coach-athlete relationship on motivation and sports engagement - Jet Longakit; Lyndie Toring-Aque; Felix Aque Jr.; Minerva Sayson; Joseph Lobo (Physical Education of Students, 2024)
Background and Study Aim. The relationship between coach and athlete may significantly influence an athlete's experience in sports. Elements such as closeness, commitment, and complementarity are key aspects of this relationship. The current study aimed to examine the association between motivation and athletes' engagement in sports, as mediated by the coach-athlete relationship.